The use of advanced communications and internet technology in car transportation to facilitate improvements for both driver and passengers - Saftah, Rehab Omar (2015)
People love and at the same time need to travel. The society grows and develops based on a distributed environment, and the people’s ability to move freely from one place to another is fundamental to keep it functional. Along with trains and commercial trucks for moving goods and materials, the car gives individuals the virtually unlimited ability to travel anywhere in the country in just a matter of hours or days. This thesis focuses on the usage of advanced communications internet technology (Internet of Things) in car transportation in order to facilitate improvements for both drivers and passenger. In particular three aspects motivated the work in the thesis: safety, comfort and convenience. In order to increase the safety, the comfort and the experience while driving, and the convenience, the proposed solution focuses on the Internet of Things (IoT) concept, applications and the advantages that it brings. In order to provide a viable and practical solution that will include all aspects of the IoT enabled car transportation, the following challenges were addressed in the thesis: safety, inconvenience, system architecture including devices/sensors, network, data management, applications and privacy, security and ethics. Then, the thesis presented a novel solutions of how the current advancements in internet communication and sensor technologies (IoT technologies) can improve the car transportation for both the driver and the passengers. In particular, the research shows how the various sensors inside and outside the car, can sense different parameters, share these between each other and this way to make decisions in order to improve the driving experience. The proposed solution is a combination between some of the methods based on existing technology which have been discovered from literature research (i.e. autonomous car), building on that many improvements, adding new innovative features, methods and applications to adapt it to our needs to solve existential problems and issues. The proposed solutions are based on a completely connected car, with practical applications of most of them in today’s transportation ecosystem. Designed on the principles of safety, comfort and convenience, it allows services in traffic management, health and other crucial areas, which were not possible previously. To summarize, this thesis proposes a novel solution which is based on the usage of the internet of things concept in car transportation. The solution proposes improved services, applications and systems which are better than the current systems. It combines different technologies, best practices and services with many of new unique and implementable ideas, features and techniques.